Prototipe Sistem Monitoring Disfungsi Traffic Light - Prasetio A, Lucky Y; Basri, Muhammad (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
One of the problems currently is that many traffic lights are not functioning properly. Handling and repair of facilities by officers is carried out periodically and awaits information from the public. It is felt to be less efficient because the number of points is very large, while the number of officers is small, which slows down handling, resulting in losses to society, such as increasing the number of traffic accidents and crime. This research aims to design a prototype traffic light dysfunction monitoring system that can monitor traffic light status in real time. The qualitative research method uses an Arduino Uno controller, ESP8266, an IoT-based voltage detector sensor, and an AC712 current sensor. The results of making the prototype make it easier for officers to monitor traffic light status in real time at observation points and can reduce the number of traffic accidents on roads that can harm the public.